2016
DOI: 10.1083/jcb.201605097
|View full text |Cite
|
Sign up to set email alerts
|

Activating the nuclear piston mechanism of 3D migration in tumor cells

Abstract: Petrie et al. show that inhibiting matrix metalloproteinases during 3D tumor cell migration activates the fibroblast-associated nuclear piston mechanism of intracellular pressure generation to slow tumor cell movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 27 publications
7
86
2
Order By: Relevance
“…However, other studies have shown that expression of integrin β3 is variable in response to other forms of mechanical stimuli in various types of cancer (Felding-Habermann et al, 2001;Page et al, 2015). Additionally, a recent study found that HT1080 cells exhibit an MMP-independent 'nuclear piston' mechanism of invasion that requires integrin β3 activity (Petrie et al, 2017). It is an intriguing possibility that a cell uses the expression of integrin β3 to select between modes of invasion, such that downregulation promotes MMP-dependent invasion while normal levels of integrin β3 expression favors an MMPindependent nuclear piston mode of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that expression of integrin β3 is variable in response to other forms of mechanical stimuli in various types of cancer (Felding-Habermann et al, 2001;Page et al, 2015). Additionally, a recent study found that HT1080 cells exhibit an MMP-independent 'nuclear piston' mechanism of invasion that requires integrin β3 activity (Petrie et al, 2017). It is an intriguing possibility that a cell uses the expression of integrin β3 to select between modes of invasion, such that downregulation promotes MMP-dependent invasion while normal levels of integrin β3 expression favors an MMPindependent nuclear piston mode of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Increased heterochromatin levels were shown to increase nuclear rigidity (Zhang et al 2016a;Furusawa et al 2015;Stephens et al 2018), which may be important to protect the genome from mechanical damage that can occur during migration through confined spaces (Denais et al 2016;Raab et al 2016). Increased nuclear rigidity may also serve as a better anchoring point for the actin cytoskeleton that was suggested to use the nucleus to generate force during cell migration (Graham et al 2018;Petrie et al 2017). In support of the at 37 O C, 7% CO2.…”
Section: Discussionmentioning
confidence: 77%
“…The malignant counterpart of normal human fibroblasts, fibrosarcoma cells, fails to undergo nuclear piston migration in a cell‐derived matrix until their protease activity is inhibited for stabilization of the adjacent extracellular matrix . In fact, treatment of cell‐derived matrix with proteases can abolish lobopodial migration by normal human fibroblasts .…”
Section: Cancermentioning
confidence: 99%